EMOTIONAL INTELLIGENCE AND LEADERSHIP IN INDIA - SWETA CHAUHAN, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2023)
This paper makes the case that the leadership process is heavily influenced by feelings (moods and emotions). More precisely, it is suggested that emotional intelligence, or the capacity to comprehend and control one's own and others' moods and emotions, plays a role in effective leadership in organisations. There are four main components of emotional intelligence: understanding and expressing emotions, using emotions to improve thinking and decision-making, knowledge of emotions, and managing emotions. Additionally, how emotional intelligence contributes to effective leadership by focusing on the five key components of effective leadership: creation of shared goals and objectives; teaching others the value of work activities; creating and maintaining enthusiasm, confidence, optimism, cooperation, and trust; encouraging flexibility in decision-making and change; and creating and upholding a meaningful identity for an organisation. The pertinent review of the literature concentrated on four main areas: the theoretical justification for studying emotional intelligence, the relationship between emotional intelligence and leadership effectiveness, effective leadership practises within private Indian organisations, and implications for organisational leadership